Improving Students’ Attitudes toward the Study of Literature in EFL Classroom: A Systemic Review - Fatma Rahayu Nita; Ali Mustofa (English Department, Faculty of Humanities, Andalas University, 2022)
Several students do not show their positive attitude in studying literature because they are getting difficulties engaging with the materials and the literary texts that are provided by the teachers. Other than that, there are various factors that influence the students not to show their positive attitude to the study of literature. Therefore, this article attempts to elaborate on two main factors that influence student attitudes in studying literature in the EFL (English as a Foreign Language) classroom and offer the strategies used to improve student attitudes in studying literature. Two main factors that affect their attitude toward the study of literature are the selection of literary texts and the teaching method used by the teachers. Thus this article elaborates on how to select the appropriate literary text to improve student attitudes toward the study of literature. Also, it offers two possibilities of teaching methods that are used to encourage the students in studying literature. It involves reading response and visual aids. To generalize the idea, in increasing student attitudes in studying literature, it needs creativity and much effort for the teachers. Students also face many difficulties in studying literature in the classroom. Thus, educators should be aware of the problems that arise among the students and provide the appropriate solution to them.